Factors Affecting Decision in Durian Purchase of Entrepreneurs in the Central Market for Agriculture, Yala Province - Phubenyapong, Teerat; Trimanee, Sunee; Thaiburi, Narid; Yusohpaluka, Sareepah; Chintapitaksakul, Parpitchaya (Princess of Naradhiwas University Journal of Humanities and Social Sciences, 2023)
The objectives of this article were 1) to study of the social and economic conditions of entrepreneurs, 2) to study the level of satisfaction of entrepreneurs in Yala Central Market and 3) to study factors affecting decision in durian purchase of entrepreneurs in the market. The samples included 70 Thai entrepreneurs who registered as durian traders with Yala City Municipality. Data was collected through interviews between July and October 2018. Data were analyzed using statistics; percentage and mean; multiple regression analysis. The results of this study showed that 1) 84.3% of entrepreneurs were males, the average age was 42.54 years, with an average annual income of BHT 226,093.91 from trading durian, having experience in trading durian approximately 10.47 years. The entrepreneurs were wholesale buyers at 84.25%, and the average amount of durian purchased per day was at 3.05 tons/day, 2) The satisfaction of entrepreneurs in Yala Central Market towards durian business showed that the aspects received the most satisfaction were price, product and channel of distribution while the marketing promotion received satisfaction at a high level, and 3) The factors influenced on durian purchase were the source, quality and experience in business with a statistical significance (p <0.01).